Evidence for generalizability of edaravone efficacy using a novel machine learning risk-based subgroup analysis tool. Issue 1 (2nd January 2022) - Brooks, Benjamin Rix; Pioro, Erik P.; Beaulieu, Danielle; Taylor, Albert A.; Schactman, Mark; Keymer, Mike; Agnese, Wendy; Perdrizet, Johnna; Apple, Stephen; Ennist, David L.
Abstract: Introduction: The edaravone development program for amyotrophic lateral sclerosis (ALS) included trials MCI186-16 (Study 16) and MCI186-19 (Study 19). A cohort enrichment strategy was based on a Study 16 post hoc analysis and applied to Study 19 to elucidate a treatment effect in that study. To determine whether the Study 19 results could be generalized to a broader ALS population, we used a machine learning (ML) model to create a novel risk-based subgroup analysis tool. Methods: A validated ML model was used to rank order all Study 16 participants by predicted time to 50% expected vital capacity. Subjects were stratified into nearest-neighbor risk-based subgroups that were systematically expanded to include the entire Study 16 population. For each subgroup, a statistical analysis generated heat maps that revealed statistically significant effect sizes. Results: A broad region of the Study 16 heat map with significant effect sizes was identified, including up to 70% of the trial population. Incorporating participants identified in the cohort enrichment strategy yielded a broad group comprising 76% of the original participants with a statistically significant treatment effect. This broad group spanned the full range of the functional score progression observed in Study 16. Conclusions: This analysis, applying predictions derived using an ML model to a novel methodology for subgroup identification, ascertained a statistically significant edaravone treatment effect in a cohort of participants with broader disease characteristics than the Study 19 inclusion criteria. This novel methodology may assist clinical interpretation of study results and potentially inform efficient future clinical trial design strategies.